1997
DOI: 10.1016/s1074-7613(00)80240-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Somatic Mutation in a Human B Cell Line In Vitro

Abstract: Both the B cell-surface trigger(s) and the intracellular molecular mechanism(s) of somatic hypermutation in immunoglobulin (Ig) variable region genes remain unknown, partly because of the lack of a simple and reproducible in vitro model. Here, we show that upon surface immunoglobulin cross-linking followed by co-culture with activated cloned T cells, the Burkitt's lymphoma cell line BL2 is induced to mutate its IgV(H) gene. Repeated activation of BL2 cells increased the frequency of mutation. The in vitro-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
2
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 57 publications
3
93
2
2
Order By: Relevance
“…Human Burkitt's lymphomas undergo SHM in culture either constitutively (Ramos cell line) or after induction (BL2 or CL-01 cell lines) [81][82][83][84] . The pattern of mutations does not mimic the SHM pattern generated in vivo as it displays more mutations at G/C base pairs (80% versus 20% at A/T base pairs).…”
Section: Polη the Study Of Patients Affected By The Xeroderma Pigmenmentioning
confidence: 99%
“…Human Burkitt's lymphomas undergo SHM in culture either constitutively (Ramos cell line) or after induction (BL2 or CL-01 cell lines) [81][82][83][84] . The pattern of mutations does not mimic the SHM pattern generated in vivo as it displays more mutations at G/C base pairs (80% versus 20% at A/T base pairs).…”
Section: Polη the Study Of Patients Affected By The Xeroderma Pigmenmentioning
confidence: 99%
“…The human Burkitt's lymphoma BL2 cell line has been described previously [14][15][16]. Cells were grown in RPMI medium supplemented with 10% heat-inactivated FBS (Invitrogen, Carlsbad, CA).…”
Section: Cell Linesmentioning
confidence: 99%
“…First, the cell line has surface markers of centroblast stage B cells [14,15], indicating that these cells are immune competent. Second, the V-region of the IgG heavy chain gene undergoes only a low rate of spontaneous mutagenesis, whereas mutagenesis can be induced ~10-fold by addition of cell surface receptor ligands, and this is considered reflective of SHM [14][15][16]. In preliminary studies, we found variability among samples of BL2 cells with regard to the amount of V-region mutations observed after induction.…”
Section: Pol β Protein Level By Immunoblottingmentioning
confidence: 99%
“…To date, studies of potential trans-acting factors in humans and mice carrying de¢ned gene disruptions have told us much about gene products which are not involved or, at least, are redundant for hypermutation and a little about those which might be (reviewed in Wood 1998). An important development for the analysis of hypermutation has been the identi¢cation of cell lines that either inducibly or constitutively hypermutate their immunoglobulin genes such that mutations can be readily assayed by DNA sequencing after short periods of culture (Dene¨poux et al 1997;Sale & Neuberger 1998;Wabl et al 1985;Zan et al 1999;Zhu et al 1995). Such models are already providing clues as to the signals required to trigger hypermutation as well as insights into the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%